BACE1 molecular docking and anti-Alzheimer's disease activities of ginsenosides. (22nd August 2016) - Choi, Ran Joo; Roy, Anupom; Jung, Hee Jin; Ali, Md. Yousof; Min, Byung-Sun; Park, Chan Hum; Yokozawa, Takako; Fan, Tai-Ping; Choi, Jae Sue; Jung, Hyun Ah
Abstract: Ethnopharmacological relevance: Ginsenosides are natural product steroid glycosides and triterpene saponins obtained from the Panax species. Panax ginseng has been widely used as a traditional Chinese medicine (TCM) for around a thousand years, especially in East Asian countries. Ginseng, the root and rhizome of the most popular species P. ginseng, used as tonic, prophylactic agent and restorative. In TCM, ginseng is highly valued herb and has been applied to a variety of pathological conditions and illnesses such as hypodynamia, anorexia, shortness of breath, palpitation, insomnia, impotence, hemorrhage and diabetes. Aim of the study: The basic aim of this study was to evaluate the anti-Alzheimer's disease activities of selected ginsenosides (Rb1, Rb2, Rc, Re, Rg1, and Rg3) according to peroxynitrite (ONOO ‒ ) scavenging activity and inhibitory activity of ONOO − -mediated nitrotyrosine formation as a measure of changes in oxidative stress. In addition, molecular docking simulation studies were performed to predict binding energies of the ginsenosides with β-site amyloid precursor protein cleaving enzyme 1 (BACE1, β-secretase) and identify the interacting residues. Materials and methods: In vitro cholinesterase enzyme assays by using acetylcholinesterase (AChE), butyrylcholinesterase( BChE), and BACE1 were performed. In vitro authentic peroxynitrite scavenging activity and inhibitory activity against ONOO − -mediated nitrotyrosine formation were also performed. Molecular docking simulation studies were performed with Autodock Vina software and Discovery studio 4.1. Results: In vitro enzyme assays demonstrated that ginsenosides have significant inhibitory potential against AChE, BChE, and BACE1, as well as ONOO − and nitrotyrosine formation. Most importantly, significant AChE inhibitory activities were observed for Re; BChE for Rg3; and BACE1 for Rc, with IC50 values of 29.86±3.20, 16.80±0.36, and 59.81±2.74 μg/mL, respectively. Among the tested ginsenosides, Rb1 exhibited a higher scavenging activity against ONOO − with an IC50 value of 27.86±1.34 μg/mL, while Rc and Rg3 exhibited impressive inhibitory activity against the formation of nitrotyrosine. In addition, molecular docking studies revealed potential BACE1 inhibitory activity of ginsenosides, especially Rb1 and Rb2, which exhibited good binding affinities towards BACE1, with docking scores of −10 kcal/mol. Conclusion: The findings of the present study suggest the potential of ginsenosides (Rb1, Rb2, Rc, Re, Rg1, and Rg3) for use in the development of therapeutic or preventive agents for Alzheimer's disease, especially through inhibition of AChE, BChE and BACE1 activities, as well as scavenging of ONOO − and inhibition of nitrotyrosine formation. Graphical abstract: